Characteristics of Gandaria (Bouea macrophylla Griff) Fruit Wine from Primary Fermentation and 14 Days Aging with Different Commercial Yeast Types and Concentrations - Moniharapon, Erynola; Tuhumury, Helen Cynthia Dewi; Souripet, Agustina (Journal of Applied Agricultural Science and Technology, 2023)
Gandaria fruit wine, however, is still made using a straightforward fermentation procedure, hence the final product is murky. The correct variables for judging fruit wine quality still require a number of optimization procedures to be carried out. The purpose of this research was, therefore, to compare the primary fermentation and aging effects of different commercial yeast types on the physicochemical properties of gandaria fruit wine. Aging for 14 days caused a significant decrease in the characteristics of gandaria wine produced with different commercial yeast types and concentrations compared to the freshly fermented wine. Total sugar, total acidity, vitamin C, total soluble solids, and turbidity were among the characteristics that decreased. Whereas with aging, the alcohol content and pH values increased. The gandaria wine produced with commercial yeast Pakmaya at a 2.5% concentration was found to be the best due to the alcohol content that complied with the standard for fruit wine and had the clearest resulting wine both for the primary fermentation and the 14-day aging.